Food safety investment expert advice: Burkina Faso, Ethiopia, Nigeria - Grace, Delia; Alonso, Silvia; Mutua, Florence K.; Roesel, Kristina; Lindahl, Johanna F.; Amenu, Kebede (International Livestock Research Institute, 2018)
This report summarises evidence and evidence gaps in order to help answer the following questions relevant to food safety investments in Ethiopia, Nigeria and Burkina Faso and more generally sub-Saharan Africa. 1. Why invest in food safety? What are the burdens of food safety? 2. Which sectors should be targeted to ensure food safety investments have greatest impact? 3. Which food safety hazards should be prioritised? 4. Which foods and value chains to invest in? 5. Which investments are most likely to succeed?